Multidimensional Assessment of Electroencephalography in the Neuromodulation of Disorders of Consciousness - Zhang, Chunyun; Han, Shuai; Li, Zean; Wang, XinJun; Lv, Chuanxiang; Zou, Xiangyun; Zhu, Fulei; Zhang, Kang; Lu, Shouyong; Bie, Li; Lv, Guoyue; Guo, Yongkun (Frontiers in Neuroscience, 2022)
To assess the changes of electroencephalography (EEG) multidimensional metrics during neuromodulation, we performed repeated stimulation using the high-density transcranial direct current stimulation (HD-tDCS) protocol in 42 patients with DOC (disorders of consciousness). Coma Recovery Scale-Revised (CRS-R) scores and EEG metrics (brain network indicators, spectral energy, and normalized spatial complexity (NSC)) were obtained before and fourteen days after HD-tDCS stimulation. CRS-R scores increased in the responders(R+) group after stimulation. R+ group showed increased spectral energy in the alpha2 and beta1 bands, mainly at the frontal and parietal electrodes. Increased graphical metrics in the alpha1, alpha2 and beta1, combined with increased NSC in the beta2 in the R+ group, suggest that improved consciousness was associated with a tendency toward stronger integration in the alpha1 band and greater isolation in the beta2. Also, using NSC as a feature to predict responsiveness by machine learning with a prediction accuracy of 0.929 demonstrated that the NSC of alpha and gamma on baseline is more important for the consciousness improvement. Modulation of the posterior lobe can lead to an EEG response related to consciousness in DOC, and the posterior cortex may be one of the key brain areas involved in the formation or maintenance of consciousness.